Obvladovanje notranje narave po Radža jogi - Milčinski, Maja (Studia mythologica Slavica, 2000)
This paper presents one of the methods of conquering one's inner nature, namely Raja Yoga or "the royal yoga", which has been often described as the most important of yogic paths. Although almost all of the schools of Indian philosophy and religion are related to yoga, this paper is focused on the classical yoga, as presented in Patanjali's Yoga sutras and in Swami Vivekananda's (1862-1902) commentaries to them. Based on the sources on which the Slovenian translation of Raja Yoga has been done, this paper also presents some aberrations between translations of these texts.
Keywords: filozofija religije; indijska filozofija; joga; radža joga